Inappropriate antibiotic prescribing in managed care subjects with influenza - Misurski, Derek A; Lipson, David A; Changolkar, Arun K (The American journal of managed care, 2011)
To evaluate costs of inappropriate oral antibiotic prescribing in a managed care population with influenza. This was a retrospective (January 1, 2005, through December 31, 2009) analysis of the US Impact National Benchmark Database. Patients with an influenza diagnosis (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] code 487.xx) and continuous health plan enrollment for >12 months before and 1 month after the index influenza diagnosis date were included. We identified patients with an antibiotic prescription claim within 3 days before or 3 days after the index influenza diagnosis date. Patients were classified as having received appropriate antibiotic treatment if a secondary respiratory infection was observed within the 2-week postindex period or if there was a previous comorbid diagnosis of diabetes, congestive heart failure, chronic obstructive pulmonary disease, asthma, acute myocardial infarction, or sickle cell anemia as identified by ICD-9-CM codes. We identified 270,057 subjects with influenza (mean age, 31.6 years). Antibiotics were prescribed in 58,477 (21.65%) patients. Among patients receiving antibiotics, 99% did not have a follow-up diagnosis for a respiratory bacterial infection and 79% had neither a secondary infection nor evidence of a comorbidity (ie, received inappropriate antibiotic treatment). Based on a conservative annual seasonal influenza rate of 10%, we estimated that inappropriate antibiotic prescribing for influenza costs the United States approximately $211 million annually. Empiric antibiotics were inappropriately prescribed in a high percentage of influenza patients. This represents a significant financial burden to the US healthcare system and may contribute to increased antibiotic resistance.